Rancang Bangun Sistem Informasi E-Commerce Jual Beli Mobil Bekas Berbasis Website - Rofiq Kusnandar; Ar Yanto (Joined Journal (Journal of Informatics Education), 2025)
The development of information technology has driven digital transformation across various sectors, including the used car trading industry, which often encounters challenges such as limited information, narrow market reach, and lack of transparency in pricing and vehicle conditions. This study aims to design and develop a web-based e-commerce information system to enhance efficiency and trust in used car transactions. The research employs the Rapid Application Development (RAD) method, utilizing an iterative approach through design, prototyping, and repeated testing to ensure the system meets user requirements. The system was built using the Laravel 11 framework with Query Builder for database management. The findings indicate that the platform facilitates easier and more structured processes of searching, booking, and conducting transactions online. The conclusion of this research is that the developed system can expand market reach, improve transaction efficiency, and provide transparency in the used car trading process. The contribution of this study lies in applying RAD for web-based e-commerce development while offering a scientific reference for further research in the field of information systems.